Pengaruh Implementasi Model Problem Based Learning Berbasis Audio Visual Terhadap Peningkatan Hasil Belajar Siswa di SMP Negeri 20 Kupang - Yulfenti Sayuna; Yeheskial Nggandung; Agustina Butar-Butar (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study addresses the issue of suboptimal student academic performance, which is frequently linked to the selection of instructional strategies that do not actively engage learners. Learning outcomes represent a multidimensional construct involving knowledge acquisition, attitude development, and skill formation. Therefore, the application of an appropriate learning model is essential to support meaningful learning experiences. This research aims to investigate the impact of implementing a Problem Based Learning (PBL) model supported by audio-visual media on students’ academic achievement. A quantitative approach with a quasi-experimental design was employed. The study involved two groups: an experimental class receiving the PBL intervention and a control class experiencing conventional instruction. Data were collected through pretest and posttest assessments and analyzed using both descriptive and inferential statistical techniques. The findings reveal a statistically significant difference between the two groups, indicated by a significance value below 0.05. This confirms that integrating problem-based strategies with audio-visual support contributes positively to improving students’ learning outcomes. The results highlight the importance of student-centered learning environments in fostering deeper understanding and engagement.